G628(P) Talk to me: exploring how doctors prescribe insulin for children. (May 2019) - Bell, A; Dornan, T; Conn, R
Abstract : Background: Insulin is a dangerous medication and prescribing errors associated with its use can lead to life-threatening consequences. Children are a patient group at increased risk of harm when medication errors arise. The success of an insulin prescription can only be assessed in retrospect and many aspects of insulin prescription are uncertain. Holistic prescribing involves not only safely prescribing a medication, but also involving the patient and their parent/carer in the process. An insulin prescription chart structures the task of prescribing but there is a lack of research on its impact on doctors' behaviours. Aim: To explore how a prescription chart structures the task of prescribing insulin. Methods: Qualitative study involving interviews with seven junior doctors who routinely prescribe insulin for children. Interviews comprised two phases: 'free association' interview where doctors described their approach to insulin prescribing; and a simulated prescribing task using think-aloud methodology, where doctors verbalised their reasoning while completing an insulin prescription chart. Interview transcripts were thematically analysed, guided by a published insulin prescribing framework. Doctors' approaches during each interview phase were compared, supported by content analysis of coded data. Results: Introducing a simulated scenario and prescription chart caused doctors to shift from a holistic to a narrower, task-focused approach to prescribing. Fewer doctors verbalised an intention to interact with patients. Despite having the chart as a prompt, they were less likely to mention checking aspects of their prescriptions. Doctors did not reflect on their own ability to prescribe in either the free association or simulated prescribing phase. Conclusion: This study shows that the use of a prescribing scenario and prescription chart changes doctors' behaviours. Training doctors to prescribe by completing charts alone may de-emphasise the importance of patient engagement. We recommend patient-centred prescribing education for medical students and doctors, involving a staged progression from prescribing in classroom settings, to prescribing with simulated patients, to opportunities to prescribe in practice under supervision. Doctors should be encouraged to reflect on their own abilities while prescribing.